Trade unions in light of civilizational changes: Opportunities, challenges, dangers - Kryszczuk, Maciej D.; Wentzel, Michał (Journal of Public Governance, 2017)
The scientific and technological revolution, as well as rapid acceleration in business processes on a global scale, affect labour and capital in an asymmetrical manner. Capital is inherently more f lexible than human beings, who, in addition to economic constraints, live in a network of social relations. The position of the working class is additionally weakened by process automation, replacing workers by increasingly intelligent robots. The authors’ intention is to sketch a sequence of cause and effect of these processes: describe the basic aspects of the transformation of the labour market, their impact on trade unions, and outline the future outlook for the trade union movement.